Iminosugars of the Invasive Arboreal Amorpha fruticosa and Glycosidase Inhibition Potential - Robert J. Nash; Barbara Bartholomew; Yana B. Penkova; Ekaterina Kozuharova (Plants)
Amorpha fruticosa L. (Fabaceae) originates from North America and has become an aggressive invasive plant in many parts of the world. It affects the local biodiversity in many negative ways. Our previous in vivo tests of purified extract of A. fruticosa pods for antihyperglycemic activity in streptozotocin-induced diabetic spontaneously hypertensive rats (SHRs) revealed that the oral administration of purified extract of A. fruticosa (100 mg/kg) for 35 days to SHRs caused significant decreases in the systolic pressure, blood glucose levels, and MDA quantity. The aim of this experimental study is to test the glycosidase inhibition of several extracts of A. fruticosa pods. Methods: GC-MS, NMR, and a glycosidase inhibition assay were performed. Results: The results demonstrate strong inhibition of yeast alpha- and almond beta-glucosidases, rat intestinal hexosaminidase, and bovine beta-glucuronidase, but not of some other glycosidases. The activity is probably due at least in part to the presence of iminosugars and iminosugar acids. We here report on further analysis and activity assessments of A. fruticosa pods and leaves collected in Bulgaria, and for the first time discover glycosidase inhibitors, pinitol, and hydroxylated pipecolic acids in the species and more complex iminosugar-like compounds that may all contribute to antidiabetic potential. Hydroxylated pipecolic acids are probable precursors of iminosugars and common in legumes containing them. Considerable chemical variation was observed over four pod collections. Conclusions: A. fruticosa pods and leaves were found to contain a number of compounds that could contribute to the potential antihyperglycemic activities including pinitol and a complex mixture of iminosugar-related compounds derived from pipecolic acids and prolines. The pods and leaves caused potent selective inhibition of glucosidases and hexosaminidases and beta-glucuronidase. The variation between the collections might reflect the sites differing or wide phenotypic versatility allowing the success of the species as an invasive plant.